1992
DOI: 10.1073/pnas.89.16.7398
|View full text |Cite|
|
Sign up to set email alerts
|

Chromostatin inhibits catecholamine secretion in adrenal chromaffin cells by activating a protein phosphatase.

Abstract: Chromostatin is a 20-residue peptide derived from chromogranin A (CGA), the major soluble component of secretory granules in adrenal meduliary chromaffin cells. One known biological function of chromostatin is to inhibit the secretagogue-evoked catecholamine secretion from chromaffin cells. Putative receptors are present on the chromaffin-cell plasma membrane, and the activation of such receptors leads to the inhibition of L-type voltage-sensitive calcium channels.We report here that exposure of chromaffin cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 43 publications
(37 reference statements)
1
9
0
Order By: Relevance
“…The data above demonstrate that at least one isoform, PP-ly, is present in both cytosolic and particulate fractions of the parathyroid; this is consistent with observations of PP-Iy in varying ratios in the soluble and particulate fractions in cortex, cerebellum, testis, spleen and adrenal [50]. Type 1 protein phosphatases have a broad range of physiological functions, including the regulation of exocytosis [51]. Parathyroid PP-ly is concentrated at the cell periphery in the vicinity of the plasma membrane; this is consistent with a role in the modulation of PTH secretion.…”
Section: Discussionsupporting
confidence: 70%
“…The data above demonstrate that at least one isoform, PP-ly, is present in both cytosolic and particulate fractions of the parathyroid; this is consistent with observations of PP-Iy in varying ratios in the soluble and particulate fractions in cortex, cerebellum, testis, spleen and adrenal [50]. Type 1 protein phosphatases have a broad range of physiological functions, including the regulation of exocytosis [51]. Parathyroid PP-ly is concentrated at the cell periphery in the vicinity of the plasma membrane; this is consistent with a role in the modulation of PTH secretion.…”
Section: Discussionsupporting
confidence: 70%
“…Bioactive chromostatin has previously been shown to derive from proteolytic cleavage of larger CGA products in v i m (4,18). Synthetic CGA,,,~,,3 inhibits CA release in isolated bovine chromaffin cells by inhibiting L-type CaZf channels (24) and appears to activate a type 2A phosphoprotein phosphatase in these cells (25). In this context, it is of interest to note that perfusion with aprotinin protected against extracellular cleavage of the larger CGAFs into the 22 to 24 kD components during basal release.…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of the bovine and mouse CGA genes revealed that the CGA gene contains eight exons (43,44 (9) by activating a protein phosphatase (45) and by decreasing calcium channel activity (46). In the pancreas, PST has been shown to inhibit glucoseinduced insulin secretion (8); the physiological function of CST in this organ has yet to be elucidated.…”
Section: Resultsmentioning
confidence: 99%